Sex steroids and potential mechanisms of non-genomic endocrine disruption in invertebrates - Janer, Gemma (Ecotoxicology (London, England), 2007)
The review reports on the presence and metabolism of sex steroids in several invertebrate species and provides detailed information on possible mechanisms of endocrine disruption other than the interaction with nuclear receptors. The presence of most vertebrate sex steroids in invertebrate tissues has been demonstrated by liquid or gas chromatography coupled to mass spectrometry. In addition, enzymatic pathways involved in the steroidogenic pathway have been described in at least some invertebrate phyla. Some endocrine disruptors induce alterations in these metabolic pathways and might lead to changes in steroid levels. Growing evidence suggests that estradiol can act through non-genomic pathways in molluscs, and that xenobiotics can as well interfere in these signalling cascades. In spite of these recent advances, most question marks on the action and function of sex steroids in invertebrates remain to be answered